2022
DOI: 10.3390/ma15238380
|View full text |Cite
|
Sign up to set email alerts
|

Fe Ions-Doped TiO2 Aerogels as Catalysts of Oxygen Reduction Reactions in Alkaline Solutions

Abstract: Aerogels have interconnected networks and preeminent pore structures. When used as the catalysts for oxygen reduction reaction (ORR), they can facilitate the mass transfer and expose more active sites. Here, we synthesized the Fe-doped titanium oxide-based aerogels (TA/Fes) by the sol–gel method combined with thermal treatment. The specific surface areas of the TA/Fes ranged from 475 to 774 m2·g−1, and the pore volumes varied from 0.96 to 1.72 cm3·g−1. The doping effect of the Fe ions and the oxygen vacancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The results showed an increase of electron density for the Ti atom in CTA-M, which may be attributed to the formation of oxygen vacancies. 12,23 Although no XRDdetectable crystalline phase has been formed, this valence state existed in the system. This is due to the fact that these two peaks originated from oxygen vacancies in the anatase crystalline form, and the appearance of oxygen vacancies leads to the transformation of Ti 4+ to Ti 3+ to fit the electrostatic equilibrium in the system, thereby leading to a transformation in the electronic structure around Ti and the emergence of peaks.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The results showed an increase of electron density for the Ti atom in CTA-M, which may be attributed to the formation of oxygen vacancies. 12,23 Although no XRDdetectable crystalline phase has been formed, this valence state existed in the system. This is due to the fact that these two peaks originated from oxygen vacancies in the anatase crystalline form, and the appearance of oxygen vacancies leads to the transformation of Ti 4+ to Ti 3+ to fit the electrostatic equilibrium in the system, thereby leading to a transformation in the electronic structure around Ti and the emergence of peaks.…”
Section: Resultsmentioning
confidence: 98%
“…In comparison to other samples, CTA-Fe-A showed better pore structure (high specific surface area and high pore volume), which enhanced the electrochemical catalytic performance, demonstrating the relationship between the catalytic performance and specific surface area and pore volume. The pore structure parameter of CTA/Sm-A is only compared to CTA-Fe-A, and its E onset and E 1/2 are improved in comparison to those of undoped samples, which are 0.82 and 0.66 V 12 . CTA-La-A and CTA-Zr-A have the worst pore structure, leading to the least E onset , E 1/2 , and J limit .…”
Section: Orr Electrocatalytic Performancementioning
confidence: 99%
See 2 more Smart Citations
“…[42][43][44][45][46] The measurement and analysis of R ct can provide an important reference for the elds of CE materials, electrochemical sensors, [47][48][49] and catalysts. 50,51 From the results, it can be found that the addition of Ti 3 C 2 T x has a signicant effect on the EIS of CEs. When the Ti 3 C 2 T x addition is 1.0 wt%, the C/T-1.0 wt% exhibits a value of R ct of only 6.64 U, which is much lower than the CNTs CE (14.39 U) and close to the performance of Pt CE (2.85 U).…”
Section: Electrochemical Performance Of the Cesmentioning
confidence: 93%